(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study included the isolation and diagnosis of the fungi from the cleaning powder in the soap(Laundries’ staff, Laundries of student). The study appeared many of the different kinds of fungi:( Absidia sp,Candidia sp, Aspergillus sp,Penicillum sp). The rate of appearance of the type of the fungi in Laundries ’ staff is the higher than the laundries’ of the students.The rate of appearance of the fungi Absidia is recoded 36.8% and Candidia ,Aspergillus niger is recoded 21.05% and Aspergillus flavus recoded 5.2 % , Penicillum sp recoded 15.7% while in the laundries of students the fungi Aspergillus niger is recorded 15.7% and the fungi Absidia ,Candidia, Apergillus terrus is recoded 20% , Penicillum sp ,Alternaria sp is recoded 10%.The study showed the influence of the heating water extract hot watering extract the race track in the concentration which is used( 10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the fungi Absidia in the concentration (30,40) mg/ml and the range of the diameter colony of the yeast Candidia albicanis in the concentration 30 mg/ml the (1)sanatamtar. While the fungi Aspergillus niger in the concentration (10,20)mg/ml is not given any resistance toward the extract.